The Effectiveness of Nursing Care: Social Isolation Implementation in Mental PMHNPM to Patient's Capability - Retty Octi Syafrini Octi Syafrini; Budi Anna Keliat; Yossie Susanti Eka Putri (Universitas Airlangga, 2015)
Introduction: Nursing care: social isolation is one of the pillars in Professional Mental Health Nursing Practice Model (PMHNPM). This study was aimed to determine the relationship between the implementation of nursing care in PMHNPM with the ability of clients and families client's. Method: This study was used a correlational design with cross-sectional approach. Samples were associate nurse who already follow PMHNPM training 58 respondents, client with social isolation problem who hospitalized at RSJD Prov. Jambi 32 respondents, and client's family 12 respondents. Independent variable was PMHNPM implementation by associate nurse, while dependent variables were the result of nursing care to client with social isolation problem and family. Data were collected by using questionnaire. Data were then analyzed by using frequency distribution for categoric data, central tendency for numeric data, and pearson correlation. Result: The results showen that nursing management capabilities signifi cantly associated (p < 0.05) with the client's ability and the ability of the family. The ability of nurses in providing nursing care social isolation were signifi cantly associated (p < 0.05) with a decrease in signs and symptoms of client upgrades. Discussion: Associate nurses ability on nursing care and PMHNPM implementation could reduce a signs and symptoms, improve an ability of the client and families client's social isolation. Keywords: PMHNPM, nursing care: social isolation, associate nurse